Cultura organizacional e a Nova Gestão Pública: uma análise de assimetria entre planejamento e execução - AMARAL, Klayrlson da Costa (Universidade Federal do Pará, 2023)
The organizational culture installed in the current Brazilian Public Administration makes it difficult to correctly measure the behavior of resource execution in the face of its institutional demands, the administrative function of strategic planning deviates in many evaluations of expenses and delivery of public policies revealing functional disagreements and negative impacts of expenses. . The complex budget system and its performance are fundamental in understanding these dysfunctions, chances in which the dissertation focused its research, applying the method in quantitative analyzes with approaches to documental and bibliographic reviews, opportunity in which planning tools, annual budget laws, management, federal government database systems and cross-sectional literature on New Public Management, converging on Neo-institutionalist and Public Choice theories, took their forms and results. In order to reach the objectives, the analysis of data confrontation by tables and graphs was carried out in a historical series of seven years of budgetary and financial execution, belonging to a unit of a federal public autarchy of education, called Campus Santana, of the Instituto Federal do Amapa. The study was limited only to the execution of current expenses, in 5 groups and elements well defined by the action codes 20RL dealt with by Law nº 4.320/64 and its amendments. The research results found significant asymmetrical levels, which revealed an average rate above thirty percent of deviation per year, configuring a performance standard that requires attention in light of efficiency and public quality, which escalated the need to characterize the organization. and understand the cultural systems that involve political-administrative and legal capacities. In the balance of practical and scientific concepts, specific lines of analysis emerged that model more realistic and compatible roles at the level of the researched structure, which in the case study enabled the proposal of a new functional model, focused on the decision-making power of resource distribution, execution and results-oriented evaluation, based on the effective participation of interest groups, management sectors, as well as local and academic representatives, which was incorporated into the legal and regulatory mechanisms to which the organization already belongs.